The response of term rates to monetary policy uncertainty - Oscar Jordá; Kevin D. Salyer (University of California, Department of Economics, 2001)
This paper shows that greater uncertainty about monetary policy can lead to a decline in nominal interest rates. In the context of a limited participation model, monetary policy uncertainty is modeled as a mean-preserving spread in the distribution for the money growth process. This increase in uncertainty lowers the yield on short-term maturity bonds because the household sector responds by increasing liquidity in the banking sector. Long-term maturity bonds also have lower yields but this decrease is a result of the effect that greater uncertainty has on the nominal intertemporal rate of substitution - which is a convex function of money growth. These predictions are broadly supported by the data: the conditional variance of monetary policy shocks identified from a conventional monetary VAR negatively affects the yields of federal funds, and the three and six-month treasury bills.
Keywords: E4; E5; E2; 330; limited participation; term structure; time-varying uncertainty; Zinsstruktur; Geldpolitik; Risiko; Dynamisches Gleichgewicht; Theorie